2023
DOI: 10.1007/s11259-023-10187-x
|View full text |Cite
|
Sign up to set email alerts
|

Non-aureus staphylococci and mammaliicocci isolated from bovine milk in Italian dairy farms: a retrospective investigation

Maria Filippa Addis,
Clara Locatelli,
Martina Penati
et al.

Abstract: Non-aureus staphylococci and mammaliicocci (NASM) are associated with bovine mastitis and increased milk somatic cell count (SCC) but their relationships with mammary gland health at the species level are not clearly defined. Regional differences have also been reported in their specific prevalence. The implementation of MALDI-TOF MS in milk microbiology is generating large and dependable datasets with the potential of providing useful epidemiological information. We present the retrospective analysis of 17,21… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…Although not as frequently as S. chromogenes and S. haemolyticus, S. microti has also been isolated from CM, SCM, and HS milk. Our two surveys indicated percentages around 1% for CM, 4% for SCM and 1.5% for HS milk (Freu et al 2023;Addis et al 2024). A recent work reported that the identi cation by MALDI-TOF MS of NASM isolated from milk as S. microti might have been subjected to misclassi cation (Kløve et al 2023).…”
Section: Introductionmentioning
confidence: 62%
See 2 more Smart Citations
“…Although not as frequently as S. chromogenes and S. haemolyticus, S. microti has also been isolated from CM, SCM, and HS milk. Our two surveys indicated percentages around 1% for CM, 4% for SCM and 1.5% for HS milk (Freu et al 2023;Addis et al 2024). A recent work reported that the identi cation by MALDI-TOF MS of NASM isolated from milk as S. microti might have been subjected to misclassi cation (Kløve et al 2023).…”
Section: Introductionmentioning
confidence: 62%
“…As in the case of S. borealis, differentiating S. rostri from S. microti and S. muscae is hampered by genetic similarity as well as by limitations in existing databases(Rosa et al 2022;Kløve et al 2023). In our previous retrospective studies, S. microti was the sixth most prevalent NASM in SCM and the ninth and tenth, respectively, in CM cases from US and Italy(Freu et al 2023;Addis et al 2024). In the present study, S. rostri accounted for 8.43% of all NASM identi ed in SCM, while S. microti was isolated only once, suggesting that previously reported S. microti might have actually been S. rostri and that the reported prevalence data for S. microti might have been overestimated.…”
mentioning
confidence: 86%
See 1 more Smart Citation
“…Though dubbed “minor pathogens”, their true impact remains debated due to their presence in both healthy and infected quarters [ 2 ]. S. chromogenes leads the pack as the most common NASM isolates [ 3 , 4 , 5 ]. Among NASM, S. chromogenes , S. simulans , and S. xylosus all raise SCC, with S. chromogenes leading in causing persistent infections [ 6 ].…”
Section: Introductionmentioning
confidence: 99%